THE INFLUENCE OF COMMUNICATIVE SKILLS AND APPEARANCE ON MANIPULATIVE MARKETING TECHNIQUES AT POINT COFFEE IN SURABAYA. - Kusmayati, Nindya Kartika (LPPM of NAROTAMA UNIVERSITY, 2024)
At this modern era, there are currently a lot of intense competition in starting a business in the field of coffee shops, especially in the Surabaya area. This research aims to explain the influence contained in the barista Point Coffee whether by having communicative skills and attractive appearance is able to influence the manipulative marketing techniques that can attract customers to purchase the product, the experiment uses correspondents totalling 33 correspondents, using a quantitative type with multiple questionnaire samples. The results of this assessment are found to come out valid and reliabaly, normatively distributed, heterosccedasticity freedom, multicoleniarity freedom, and autocollinearity freedom. Obtained multiple linear models Y 2.087 + 0.552X1 + 0.499X2 + e. with overall f test results Communicative skills (X1) and appearance (X2) have a simultaneous effect with marketing manipulative techniques (Y). As well as communicative skills (X1) have a significant impact with Manipulative Marketing (Y) at Point Coffee Surabaya and attractive appearance (X2) has a significant impact with Manipulative Marketing (Y) at Point Coffee Surabaya. Based on this, the companies also needed attention to their Human Resources to develop and improve the progress of companies engaged in coffee shops.